HUBUNGAN TIMBAL BALIK ANTARA ARUS MASUK FOREIGN DIRECT INVESTMENT DAN HUMAN CAPITAL DI INDONESIA DAN INDIA - Raden Fiat Mahadhika Ramzy (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
Foreign Direct Investment (FDI) benefits the host country by technology transfer and spillover effect toward its workforce. Meanwhile, the quality of human capital (HC) in the host country may attract FDI. This study aims to examine the relationship of FDI inflow and the quality of HC in Indonesia and India and to investigate FDI orientation. Applied two-stage least square to time series data of the year 2000-2015, the result shows a causal relationship between FDI and HC in Indonesia, but one-way relationship from FDI to HC in India. Government spending on education and health has positive effects on HC in both countries. In Indonesia, FDI is positively affected by HC and growth, while in India, only by country risk index.Keywords: Foreign Direct Investment, human capital, two stage least square